Karyotype analysis in several South American species of Solanum and Lycianthes rantonnei (Solanaceae) - Acosta, María Cristina (2005)
Somatic chromosomes of 17 species belonging to 4 subgenera and 7 sections of Solanum and Lycianthes rantonnei are studied. All taxa have 2n = 24. The chromosome numbers of S. tripartitum, S. tenuispinum, and S. vaillantii are reported for the first time, and the karyotype analysis of L. rantonnei is the first one for the genus. Morphometric chromosome analyses bring estimates of karyotype composition and asymmetry. In general, karyotypes are symmetrical with the chromosomes smaller than 4 µm long, being metacentric (69%), submetacentric (24%), or more rarely subtelocentric (7%). Solanum tucumanense, S. palinacanthum, and Solanum sp. (Acanthophora) are unique by having mostly sm and st chromosomes. All species have nucleolar organizing regions and attached satellites of variable size on short arms of one chromosome pair, usually sm or st. All species can be cytologically distinguished. Karyotype data do not allow separation of L. rantonnei from species of Solanum. Results support the validity of S. tucumanense with respect to S. pseudocapsicum. Using chromosome data exclusively, cluster analysis in 10 species from Solanum subgen. eptostemonum reinforce the systematic arrangement of taxa in subsections based on morphological features. Because of its increased karyotype asymmetry, section Acanthophora appears to be an advanced taxon within subgen. Leptostemonum.